Printability of variative nanocellulose derived papers - ÖZCAN, ARİF; ARMAN KANDIRMAZ, EMİNE (SPRINGER, 2021)
The printability properties of the paper can be increased by some processes applied to the surface. The use of non-recyclable materials derived from petroleum is decreasing day by day, and the demand for recyclable materials obtained from renewable sources is increasing. These materials include cellulose derivatives, starch types and polyvinyl alcohol. The materials ratios, sizes, physical and chemical properties of these materials used in the processes applied to the paper and the content of the paper will affect the strength of the paper as well as change the surface properties and significantly affect the printability. The aim of this study is to obtain better printability properties by improving the paper surface with CNF/CNF-OX coating. In this study, fluting and core board papers coated with different amounts of cellulose nanofiber (CNF)/cellulose nanofiber-oxidized (CNF-OX) were produced. Surface properties, contact angle, surface energy, color and gloss of the produced papers were measured by optical microscope, goniometer, spectrophotometer and glossmeter. The papers were printed with the IGT C1 offset printability tester. As a result, in terms of printability, it was determined that CNF/CNF-OX coated papers have smoother surfaces and give better results in terms of both gloss properties and printability. [GRAPHICS] .
Keywords: Cellulose nanofiber; Cellulose nanofiber-oxidized; Nanocellulose; Paper coating; Printability